Literasi Lingkungan Siswa SMA Negeri 6 Wajo Provinsi Sulawesi Selatan - Ayu Ashari; Sjaeful Anwar; Omay Sumarna (Postgraduate, University of Mataram, 2023)
This study aims to determine the level of environmental literacy of students. Research using descriptive quantitative research methods. The respondents of this study were 110 class XII students at SMA Negeri 6 Wajo. The data collection technique uses environmental literacy instruments based on aspects of environmental literacy by NAAEE (North American Association for Environmental Education) consisting of cognitive aspects, attitude, and behavior. Measurement of cognitive aspects using questions while aspects of attitudes and behavior using a questionnaire with a scale Likert. The results showed that the environmental literacy of class XII students at SMA Negeri 6 Wajo as a whole (71.3%) was in the medium category with details of cognitive aspects (50.0%) being in the medium category, attitude aspects (84.1%) being in high category and behavior (78.7%) is in the high category.